Pengaruh Product Placement Kopiko Blister Pack Dalam Drama Korea Vincenzo Terhadap Minat Beli Followers Twitter @Kdrama_Menfess - Amanda Dwi Natasha; Ikhma Zurani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research aimed to ascertain the impact of product placement of the kopiko blister pack on Twitter followers @kdrama menfess' purchasing interest in the Korean drama Vincenzo. This research intended the attention, interest, search, action, and share (AISAS) theory provides the theoretical framework for this investigation. The population in this research were the followers of twitter account @kdrama_menfess who watched the korean drama Vincenzo and aware of any kopiko blister pack product placement in that drama. A sample size of 400 respondents was obtained for this study using the sampling method of purposive sampling. The metodology of this research is quantitative, and the approach used in this research is explanatory. A questionnaire was utilized as the data collection method, which was then tested for validity and reliability. In this research, the data analysis technique is a simple linear regression test and a determination test calculated with the SPSS for Windows application. Based on the results of data processing in this research, it can be concluded that: a) there is an effect of product placement of the kopiko blister pack in the Korean drama Vincenzo on the purchasing interest of followers on the Twitter account @kdrama_menfess; and b) there is an effect of product placement of the kopiko blister pack in the Korean drama Vincenzo on the purchasing interest of followers on the twitter account @kdrama_menfess. The correlation between the independent variable and the dependent variable is shown by the R value, which is 0.811 and the R square is 0.658 with a percentage of 65.8 percent, indicating that the product placement of the kopiko blister pack in the Korean drama Vincenzo has a strong effect on buying interest in followers of the @kdrama_menfess Twitter base account.